The Effect of Operational Audit and Internal Control on Raw Material Inventory Management - Marpaung, Samuel Ariaputradana; Siagian, Harlyn L.; Manalu, Herold Moody (Institut Bisnis dan Informatika Kesatuan, 2024)
Economic developments in this era are in line with world developments which give rise to competition between companies and require company management to make the best decisions. The aim of this research is to analyze how much influence operational audits and internal control have on raw material inventory management. In this research, a quantitative method was applied where data was collected using a questionnaire, which was then processed using the SPSS data analysis tool. The research target was employees who worked at the house property company at PT Baritana Indah Persada Medan, with a total sample of 60 respondents. The data analysis methods applied in this research include descriptive statistics, classical assumption analysis, multiple linear regression, classical assumption analysis, hypothesis testing and coefficient of determination. The findings of this research reveal that there is a significant relationship between raw material inventory management and operational audits and internal controls to smooth the company's operations well.